STRATEGI PERSONAL BRANDING WALIKOTA SURABAYA CAK ARMUJI PADA AKUN TIKTOK @cakj1 - Fitriawardhani, Tira; Muhammad Fadeli; Joanna Adelaida Prigelia Salindeho (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
Some tiktok users use these applications creatively to remind themselves of society. As does in his tyres mayor Surabaya city @cakj1, he is flushing himself through the content he gives him. The research aims to endear content in tiktok @cakj1 to determine strategy personal branding an armuji on Surabaya citizens. In the study, the author employed the qualitative method of analyzing content with Peter montoya 2002's theory approach explaining that there are eight personal branding concepts, spesilization, leadership, differences, visibility, unity, and firmness a good name, through the content observation uploaded in ticktock @cakj1 and previous research and used the documentary study of screeenshoot social media content @cakj1 as a supplement to the study. The contents is "mediating conflict" and "sidak" content that draws much attention from surabaya. Through analysis, Armuji attempts to identify personal branding as a deputy mayor of the surabaya community who courageously leads the way, by trying to respond to any aspirations of surabaya's citizens quickly and defend justice and be a helper to the common people. Keywords: Personal Branding, Attracting Attention, Content, Tiktok.